INTERPRETACIÓN, LENGUAJE Y TEORÍA POLÍTICA - Rodríguez Z., José Miguel (1995)
This paper proposes a criterion to analyse the structure of the valid politic theory and its restructuration process. From hermeneutic and linguistics, concludes with a version of formalized political tbeory.